PENGARUH RISK BASED CAPITAL DAN PENDAPATAN INVESTASI TERHADAP RETURN ON ASSET - Hanafi Hanafi; Diding Apendi (UIN Sultan Maulana Hasanuddin Banten, 2019)
Risk Based Capital is a ratio to measure the level of capital adequacy in insurance companies. Insurance income is one of them from investment income, because insurance operations by investing their assets in order to generate profits. Return On Asset is a ratio that describes insurance in managing funds invested in overall assets. The formulation of the problem in the study: 1). How does the effect of risk based capital and investment income partially affect the return on assets of insurance companies in the FSA 2013-2018? 2). How does the effect of risk based capital and investment income simultaneously affect the return on assets of the Insurance Company in OJK 2013-2018? 3). How much influence does risk based capital and investment income have on return on assets for insurance companies in the OJK 2013-2018? This research uses quantitative methods with multiple linear regression analysis. Conclusion Hypothesis testing shows the value of tcount for risk based capital variable tcount risk based capital of -2.488. t table is 2.018082. So t arithmetic -2.488 <table 2.018082, Ho is accepted, risk based capital affects the return on assets. And the Investment Income of tcount is -0,993. Obtained t table is 2.018082. So t arithmetic -0.993 <table 2.018082, Ho is accepted, there is no real influence between investment income and return on assets. Fcount 3.610 and F table 3.22. Ho is rejected independent variables significantly influence the dependent variable. Risk Based Capital and Investment Income influence on Return On Assets (ROA) of 16%.